Innovative Data Collection Methods for Advancing Coastal Management in Liberia (International Journal of Scientific Research and Management (IJSRM), 2024)
Effective coastal management is crucial for the sustainability of ecosystems and the livelihoods of communities that depend on coastal resources. In Liberia, current challenges such as outdated data collection methods, limited technological resources, and inadequate community engagement significantly hinder effective decision-making and coastal management efforts. This research explores innovative data collection methods, including remote sensing, crowdsourced data collection, swarm drones, and bioacoustic monitoring as potential solutions to these challenges. By integrating these technologies, Liberia can enhance data accuracy and cost-effectiveness while empowering local communities to actively participate in sustainable practices. The adoption of these methods will not only improve the management of coastal resources but also foster resilience against climate change and environmental degradation, paving the way for a sustainable future for Liberia’s coastal regions